FaceLogix: Face Recognition Employee Attendance System with Redundancy Webcam for MD1010 Engineering - Ngah, Ahmad Firdaus; Abdullah , Nurul Azma (Applied Information Technology And Computer Science, 2024)
Systems for keeping track of and monitoring Systems for keeping track of and monitoring employee attendance are important. The employer can keep an eye on the working hours and late arrivals of their employees according to these techniques. MD1010 Engineering is a company capable of carrying out civil engineering, electrical and telecommunication work as well as building, facility, and area maintenance that still use outdated methods of attendance system. The current problem with the attendance system is that the punch card machine employed in the outdated attendance system. However, this problem may lead to chances of fake attendance such as proxy attendance and human error in data entry. Therefore. Using a face recognition system is a better way. It is more reliable and makes the attendance system easier. It also eliminates the chances of fake attendance and avoids the problems with punch cards. It is a good way for MD1010 Engineering to have a more efficient and secure system for attendance systems.